TANTANGAN DAN ADAPTASI PENDIDIKAN AGAMA ISLAM DALAM MENGHADAPI DISRUPSI KECERDASAN BUATAN (AI) - Riansyah; Oyoh Bariah; Kasja Eki Waluyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rise of Artificial Intelligence (AI) is reshaping teaching and learning practices across nearly every level of education, including Islamic religious education (Pendidikan Agama Islam/PAI). While AI offers considerable convenience, its rapid adoption raises concern over whether Islamic values can be sustained amid accelerating digitalization. This article sets out to map the challenges that AI disruption poses for PAI and to propose adaptation measures that Islamic educational institutions can pursue. The study applies a qualitative approach through library research, reviewing, comparing, and synthesizing findings from SINTA-accredited and reputable international journal articles concerning AI and PAI. The findings indicate that AI contributes positively to PAI through adaptive learning, interactive media, chatbot-based religious consultation services, and more measurable learning evaluation. At the same time, four fundamental challenges emerge: gaps in teachers' digital competence, risks to academic integrity such as plagiarism, uneven technological infrastructure across regions, and a decline in the personal teacher-student interaction that has long served as the primary vehicle for instilling religious values. In response, this study proposes four adaptation measures: strengthening digital literacy, repositioning the teacher's role as facilitator, adjusting the PAI curriculum to accommodate technology without diluting its value content, and enforcing digital ethics through collaboration among stakeholders. The study concludes that PAI's success in facing AI disruption depends not on how advanced the technology is, but on the ability of educational institutions to position AI as a supporting tool (wasilah) rather than a replacement for the teacher's role as a moral and spiritual guide.